2010
DOI: 10.1155/2010/313280
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Hepatic Veno-Occlusive Disease in Western Afghanistan Associated with Exposure to Wheat Flour Contaminated with Pyrrolizidine Alkaloids

Abstract: Pyrrolizidine alakloids (PAs) are known to cause hepatic veno-occlusive disease (VOD). Outbreaks have occurred in Western Afghanistan since 1974, the latest in February 2008. We conducted an outbreak investigation using a case-control design. Sixty-seven cases of VOD were compared with 199 community controls. Consumption of bread was strongly associated with disease (adjusted odds ratio: 35.8 [95%CI: 7.6–168.2]). Toxic doses of PA were found in plant extracts and in samples of wheat flour taken from the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 6 publications
2
116
0
4
Order By: Relevance
“…Genera of each of these plant families such as Senecio, Eupatorium, Heliotropium, and Crotalaria have been reported as toxic to livestock and humans (Mohabbat et al 1976;Tandon et al 1976;Harper et al 1985;Hill et al 1997;Prakash et al 1999;Shimshoni et al 2015b;Kakar et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Genera of each of these plant families such as Senecio, Eupatorium, Heliotropium, and Crotalaria have been reported as toxic to livestock and humans (Mohabbat et al 1976;Tandon et al 1976;Harper et al 1985;Hill et al 1997;Prakash et al 1999;Shimshoni et al 2015b;Kakar et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to wheat flour there was 1000 times less PAs in milk and whey. In water samples PAs were not detected (Kakar et al, 2010).…”
Section: Outbreaksmentioning
confidence: 90%
“…In particular, human poisoning with 1,2-unsaturated PAs is known to cause liver toxicity resulting in development of hepatic veno-occlusive disease (HVOD) (Chen and Huo, 2010). The latest documented outbreak was recorded in Afghanistan in 2008 (Kakar et al, 2010) where flour contaminated with seeds of Heliotropium (Boraginaceae) and milk from goats appeared to be the main cause for the health damage. In laboratory experiments, 1,2-unsaturated PAs showed the potential to induce genotoxicity in different model systems, and carcinogenicity was observed following chronic oral exposure to several 1,2-unsaturated PAs (Fu et al, 2004;.…”
Section: Terms Of Reference As Provided By the European Commissionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unknown whether the applied heating and fermentation processes will lead to a reduction of the PA concentration and/or changes in the PA composition. A certain stability to processing can be assumed, given that Mulder et al (2015) detected PAs in heat-treated milk from retail in the EU and Kakar et al (2010) reported occurrence of PAs in qurut, a goat cheese from Afghanistan (Kakar et al 2010).…”
Section: Introductionmentioning
confidence: 99%